An Overview of the Protein Binding of Cephalosporins in Human Body Fluids: A Systematic Review - Jongmans, C.; Muller, A. E.; Van Den Broek, P.; Cruz De Almeida, B. De Melo; Van Den Berg, C.; Van Oldenrijk, J.; Bos, P. K.; Koch, B. C. P. (Frontiers in Pharmacology, 2022)
Introduction: Protein binding can diminish the pharmacological effect of beta-lactam antibiotics. Only the free fraction has an antibacterial effect. The aim of this systematic literature review was to give an overview of the current knowledge of protein binding of cephalosporins in human body fluids as well as to describe patient characteristics influencing the level of protein binding. Method: A systematic literature search was performed in Embase, Medline ALL, Web of Science Core Collection and the Cochrane Central Register of Controlled Trials with the following search terms: “protein binding”, “beta-lactam antibiotic”, and “body fluid”. Only studies were included where protein binding was measured in humans in vivo Results: The majority of studies reporting protein binding were performed in serum or plasma . Other fluids included pericardial fluid, blister fluid, bronchial secretion, pleural exudate, wound exudate, cerebrospinal fluid, dialysate and peritoneal fluid. Protein binding differs between diverse cephalosporins and between different patient categories. For cefazolin, ceftriaxone, cefpiramide and cefonicid a non-linear pattern in protein binding in serum or plasma was described. Several patient characteristics were associated with low serum albumin.